Preparation of ferroelectric CaBi(4)Ti(4)O(15) powders from novel hydroxide precursors - Deshmukh, Rupali G.; Vaishampayan, Mukta V.; Darshane, Sonali L.; Mulla, Imtiaz S.; Gaikwad, A. B.; Rao, N. Kotaserwara; Ravi, V. (Materials Letters, 2008)
Ferroelectric CaBi(4)Ti(4)O(15) (CBT) powders were prepared for the first time from their respective hydroxides. Commercially purchased Ca(OH)(2) is mixed thoroughly with freshly prepared Bi(OH)(3) and Ti(OH)(4) in stoichiometrie ratio and heated at different temperatures ranging from 100 to 600 degrees C. The CBT phase found to be formed at 500 degrees C by the X-ray diffraction studies. This is the lowest temperature so far reported in the literature for the formation of CBT phase. The advantage of this method is that it also avoids the formation of calcium carbonate phase during synthesis. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD) method. The average particle size and morphology were studied by scanning electron microscopy (SEM) technique. (c) 2007 Elsevier B.V All rights reserved.
Keywords: CaBi(4)Ti(4)O(15); Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray methods